Synthesis and photoluminescence properties of erbium oxide thin films prepared by sol-gel method. Issue 1 (January 2018) - Chang, Yu-Hsu; Chou, Mei-Hua; Wang, Tzyy-Jiann
Abstract: This study used the sol-gel reaction to synthesize an erbium oxide precursor. The precursor was coated on a hydrophilic SiO2 /Si substrate by using spin coating technology, which was then processed at the temperature of 600–1100 °C for 45 min to form erbium oxide and erbium silicate thin films. The film obtained from a 600 °C reaction is smooth and crack-free, and it binds well to the substrate. A grazing incidence X-ray diffractometer, scanning electron microscope, and photoluminescence spectrometer were used to analyze the material structure, appearance, and optical properties of each film that was obtained and to compare the effects of different reaction conditions on material structure and optical properties. The results indicated that the Er2 O3 films fabricated by 1000 °C annealing will subsequently form Er2 SiO5 after reacting with SiO2 and were characterized by optimal luminescent properties, which made them applicable for use in future optoelectronic devices. Highlights: This is the first study using sol-gel reaction combined with spin coating technology to synthesize Er2 O3 thin films on SiO2 /Si substrate for optical property measurement. Photoluminescence characteristics of the Er2 O3 thin films in visible and near IR regions are measured and discussed in this study.